ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR MATEMATIKA SISWA SMK AVICENA TENJO - Yoyok Hariyanto; R Aditama; Yulianti Rusdiana (LPPM Universitas Bina Bangsa, 2022)
Mathematics is one of the national content subjects with the lowest index value in Avicenna Tenjo Vocational School, this is due to the lack of interest or motivation of students. Motivation is a key factor in the success of learning to try to improve and achieve learning objectives. This quantitative examination expects to gather data about the variables that impact understudy inspiration of Avicena Tenjo Professional School towards arithmetic tasks and to decide the degree of understudy inspiration. This study involved 169 grade XII students as research subjects. Motivation data obtained from questionnaires. The data collected were analyzed using descriptive statistics in the form of Logistics Ordina Regression. The results of this study note that the motivation of class XII students of Avicenna Tenjo Vocational School in the High Motivation category is 48.8% and is influenced by three main factors, namely, Teacher Follow-Up, School Environment and Parental Support. The tracking of this research should be optimized through teachers monitoring student work so that students can be more motivated in mathematics. In the school environment, students have freedom of opinion and form more independence